Alternative green extraction techniques to enhance recovery of antioxidant compounds from red peel prickly pear (Opuntia ficus-indica L. Miller) - Zirena Vilca, Franz (2024)
Prickly pear (Opuntia ficus-indica L. Miller) is a natural source of antioxidant compounds that have gained significant attention due to their potential health benefits. This study aims to investigate the effectiveness of pressurized liquid extraction (PLE) and Ultrasound-Assisted Extraction (UAE), combined with water–ethanol mixtures from 0 to 60%, at moderate temperatures between 50 °C to 70 °C to improve the recovery of antioxidant compounds from red peel prickly pear. The recovery of these compounds was affected by solvent composition and temperature for both extraction techniques. Interestingly, the use of pure water at 70 °C during the PLE process allowed the recovery of high concentrations of antioxidant compounds (12.96 mg GAE/g dw, IC5O: 2.03 mg/mL, ORAC: 625 µmol TE/g dw). On the contrary, when the UAE process was combined with 30% ethanol at 50 °C, the extractability of these compounds (10.52 mg GAE/g dw, IC5O: 3.09 mg/mL, ORAC: 561.26 µmol TE/g dw) was improved. In addition, different solvent compositions were identified to improve the recovery of specific polyphenols. For PLE, pure water at 70 °C was effective in recovering phenolic acids, flavanols, and flavonols, while the highest concentrations of stilbenes were obtained with 60% ethanol at 70 °C. For UAE, the use of 30% ethanol at 50 °C was more effective in extracting phenolic acids and stilbenes, whereas pure water at 50 °C provided high concentrations of flavanols and flavonols. These results contribute to the development of sustainable and efficient extraction strategies for obtaining antioxidant-rich extracts from prickly pear peel with important applications in functional foods, nutraceuticals, and pharmaceutical industries.